RUTILE/MELT PARTITION COEFFICIENTS FOR TRACE ELEMENTS AND AN ASSESSMENT OF THE INFLUENCE OF RUTILE ON THE TRACE ELEMENT CHARACTERISTICS OF SUBDUCTION ZONE MAGMAS - Foley S.F.; Barth M.G.; Jenner G.A. (My University, 2000)
Fractionation of some or all of the high field strength elements (HFSE) Nb, Ta, Zr, Hf, and Ti relative to other trace elements occurs in igneous rocks from convergent margins and in the average continental crust, and is generally attributed to a process occurring during subduction. The experimental partitioning of an extensive array of trace elements between rutile/melt pairs is presented which enables the effect of rutile during melting in subduction zones to be directly assessed. DNb and DTa are in the range 100-500, DZr and DHf are about 5, whereas all other trace elements analyzed have Drutile/melt less than 0.1. Published D patterns for Nb and Ta between rutile and water-rich fluids are similar to those for melt, whereas the values for Zr and Hf are significantly higher. DNb and DTa values for clinopyroxene and garnet are much lower than for rutile, and cannot cause the fractionation of HFSE from other elements seen in island arcs. The presence of rutile in the subducted slab residue during dehydration may be essential in the production of the geochemical signatures of arc magmas, whereas that of the continental crust, including higher Zr/Sm, may be produced by melting of eclogite.